SUNSCREEN CREAM BASED ON LOCAL RAW MATERIALS OF Sonneratia alba FROM TARAKAN CITY - Satriani, Gloria Ika; Ihsan, Burhanuddin; Yulma, Yulma; Rukisah, Rukisah (Jurusan Perikanan dan Kelautan, 2018)
Abstrak Traditional products derived from the local wisdom of the Tarakan City coastal communities, namely in the form of cold protective skin powder from the sun which is made from mangrove raw Sonneratia alba. This product has potential to be developed to improve the economic value of local communities. They can compete with products other sunscreen products produced by industry (commercial) through cream preparation technology (sunscreen).This research was carried out for seven months (February-August 2018) in the Environmental Laboratory of FPIK UBT, Samarinda Pharmacy laboratory (AKFARSAM), and the UNMUL Mathematics and Biochemistry laboratory. The research procedure used maserasi method with 70% ethanol solvent followed by concentrating the extract using a rotary evaporator to obtain extracts of active ingredients and carried out qualitative phytochemical testing. The obtained active ingredient was is then formulated into a sunscreen cream preparation. The level of protection of mixed sunscreen cold powder and commercial cream were tested by using UV-VIS spectrophotometer to see the value of Sun Protection Factor (SPF) at absorbance of 290-320 nm. Qualitative phytochemical test showed that on S.alba contains of positive alkaloids, phenols, flavonoids, steroids, and tannins, and negative saponins. ANOVA statistical analysis (95%) based on the calculated F value <F table so that H1 is rejected and H0 is accepted, ie there is no difference in SPF values among sunscreen products tested in this study. Based on the category of sunscreen ability, it is known that the SPF value of the three different products tested in this study ranged from maximum to ultra categories with pH values ranging from 6.5-7.5.